HEDONISM IN KEVIN KWAN’S “CRAZY RICH ASIANS” - MUHAMMAD LUTFI OBBI KUSUMA; Winda Setiasari (Universitas Negeri Medan, 2020)
This thesis deals with the hedonism in ‘Crazy Rich Asians’ novel by Kevin Kwan. The objectives are to find out the hedonism values and the influence of hedonism from the main character of the novel, which the writer wants to convey to the readers. The study was conducted by applying qualitative research. Data that uses this study are primary data: the data were reached from the ‘Crazy Rich Asians’’ novel. Then, secondary data were reached from literature review, and other sources information that related to object of this research. The technique for collecting the data was documentary technique. After analyzing the novel, it was found six of hedonism values, they are: (1). Materialism 5 cases, (2). Consumerism 10 cases, (3). Egoism 4 cases, (4). Individualism 2 cases, (5). Uncontrolled Lifestyle 10 cases, (6). Irresponsibility 3 cases. The influence of hedonism can be seen by the main character descriptions with the cases of a narration and dialogues, the writer concludes some influence of hedonism that have a bad behaviour and personalities to the readers they are. (1). Alcoholics drinks and party becomes a part of new lifestyle, (2). The concept of free love custom for teenagers (3). Earn the money to get a statisfication, (4). Wastes the time by doing unimportant things. The last the reason hedonism portrayed by the main character are found from their own surroundings such as a friends, social condition or environments, even it cames from themselves.